Microsoft SharePoint 2010 and Windows PowerShell 2.0 : expert cookbook : 50 advanced recipes for administrators and IT pros to master Microsoft SharePoint 2010 and Microsoft PowerShell 2.0 automation /: expert cookbook : 50 advanced recipes for administrators and IT pros to master Microsoft SharePoint 2010 and Microsoft PowerShell 2.0 automation. (©2011) - Unknown
No abstract available